Loudness dependence of auditory evoked potentials reflects trait anxiety and harm avoidance in healthy adults: an exploratory study - Fujita, Kohei; Takeuchi, Nobuyuki; Sugiyama, Shunsuke; Inui, Koji; Fujita, Yuki; Yamaba, Ami; Kamiya, Taeko; Ushida, Takahiro; Kanemoto, Kousuke; Miyata, Jun; Nishihara, Makoto (Frontiers in Human Neuroscience, 2025)
Loudness dependence of auditory-evoked potentials (LDAEP), a neurophysiological measure that reflects central serotonergic activity, is also influenced by the noradrenaline and dopamine systems. While it has been used in investigations of various psychiatric disorders, the fundamental characteristics in healthy individuals remain largely unknown. The present exploratory study examined 60 healthy adults to determine the associations of LDAEP with psychological traits assessed using the Temperament and Character Inventory (TCI) and State-Trait Anxiety Inventory (STAI). The participants completed TCI and STAI questionnaires before undergoing electrophysiological recordings. LDAEP was measured based on the peak-to-peak amplitude slopes of P50/N100 and N100/P200 across five sound intensity levels. Using Spearman's correlation analysis, moderate negative correlations of LDAEP slopes with harm avoidance (HA) and trait anxiety (STAI-T) scores were noted. Additionally, sex-adjusted analysis showed novelty seeking to be positively associated with LDAEP. These findings suggest an association of LDAEP with individual differences in harm avoidance, trait anxiety, and novelty seeking in healthy adults. This supports the potential use of LDAEP as a non-invasive biomarker to predict treatment response in major depressive disorder, as well as in anxiety-related conditions.